Crisis construal in the North Atlantic Financial Crisis and the Eurozone crisis. (April 2015) - Jessop, Bob
Cultural political economy integrates research on sense and meaning-making into analysis of the basic features of capital accumulation, including its contradictions, crisis tendencies and crisis dynamics. This article applies this approach to the objective overdetermination and subjective indeterminacy of economic crises. This dual character means that struggles over crisis construal shape the nature and relative success, if any, of efforts at crisis management. An important aspect of this process is the nature of learning in, through and from crisis. The article illustrates the cultural political economy (CPE) approach by examining crisis construals and crisis management in the North Atlantic Financial Crisis and the Eurozone crisis. It ends with some general remarks on the CPE approach to the articulation of crisis construals and crisis management.